A novel music-based therapeutic approach: the Therapeutic Music Listening - Raglio, Alfredo (Frontiers in Human Neuroscience, 2023)
The therapeutic use of music is frequently based on active interventions that directly involve the patient through a sonorous-music interaction with the music therapist. In contrast, approaches based on musical listening are characterized by a relationship aimed at promoting an introspective work and processing of one’s emotional experiences. Increasingly, the scientific literature has shown how even listening to music related to the patient’s personal tastes (preferred music listening) and by-passing the direct relationship with the patient, can produce therapeutic effects in different clinical settings. However, in many cases, a clear therapeutic rationale and specific application protocols are still lacking. The paper introduces a novel approach based on music listening: the Therapeutic Music Listening. This approach integrates the subjective component of listening (patient’s musical tastes) and structural and parametric characteristics of the music in relation to the therapeutic aims. The article defines theoretical-applicative bases as well as therapeutic and research perspectives of this music listening-based intervention.